Substance use and universal access to HIV testing and treatment in sub-Saharan Africa: implications and research priorities - Kathryn E. Lancaster; Angela Hetrick; Antoine Jaquet; Adebola Adedimeji; Lukoye Atwoli; Donn J. Colby; Angel M. Mayor; Angela Parcesepe; Jennifer Syvertsen (Elsevier, 2018)
As universal testing and treatment for HIV, or 'treat all', expands across sub-Saharan Africa (SSA), substance use will likely have a negative impact on the success of scale-up efforts for antiretroviral treatment (ART). Overwhelming evidence highlights the negative impact of substance use on HIV care and treatment outcomes. Yet, as many countries in SSA expand ART, evidence of the extent of substance use, and its impact in the region, is more limited. Stigma, and the psychoactive effects of substance use, are barriers to seeking HIV treatment and adhering to ART regimens for persons with heavy alcohol use or substance use. As a result, we identified several implementation and operations research priorities and metrics for monitoring the impact of substance use and Treat All. Identifying barriers and facilitators to the integration of the prevention and treatment of substance use with HIV care, and assessing effects on HIV outcomes, through longitudinal studies are priorities that will determine the impacts of substance use on 'treat all' in SSA. Future research must use existing infrastructure, including large networks of HIV clinics, to enhance our understanding of the implementation and service delivery of substance use screening, referral and treatment. These networks will also inform robust and standardised substance use estimates and interventions within the 'treat all' era in SSA.